FUNDAMENTAL RIGHT TO NON-MANIPULATION: A NEW FRONTIER OF PERSONALITY RIGHTS IN THE DIGITAL AGE - Carvalho, John Ross Silva; Cruz, Marcos Filipe Machado; Pereira, Kárita Carneiro; Rodrigues, Thallita Muriel Cardoso; Sampaio, Hermison Victor Pereira Alencar (Veredas do Direito, 2026)
This article examines one of the most subtle yet profound transformations of contemporary Brazilian democracy: the gradual replacement of overt public deliberation by concealed forms of algorithmic governance, in which political microtargeting assumes a central role in electoral influence. This dynamic displaces the exercise of political freedom of expression from the shared public sphere into private and opaque circuits, where rational persuasion gives way to the calculated exploitation of behavioral predispositions and cognitive vulnerabilities. As a result, acute constitutional tensions emerge between freedom of expression, informational self-determination, and the very integrity of the democratic process, calling into question the normative foundations of the Democratic Rule of Law enshrined in the 1988 Federal Constitution. We argue that the preservation of Brazilian democracy requires the development of more robust legal instruments aimed at algorithmic accountability and the protection of the public sphere as a collective constitutional good. The research adopts a deductive methodological approach, grounded in an extensive review of both national and international scholarship, as well as a critical analysis of the Brazilian regulatory framework, with particular attention to the General Data Protection Law (Lei Geral de Proteção de Dados Pessoais) and electoral legislation. We find that the structural opacity of algorithmic systems employed in electoral campaigns significantly hinders social, administrative, and judicial oversight of these practices, thereby enabling sophisticated and diffuse forms of public opinion manipulation that frequently evade traditional mechanisms of legal accountability.